Understanding the Complex Milieu of Epithelial-Mesenchymal Transition in Cancer Metastasis: New Insight Into the Roles of Transcription Factors - Imodoye, Sikiru O.; Adedokun, Kamoru A.; Muhammed, Abdurrasheed Ola; Bello, Ibrahim O.; Muhibi, Musa A.; Oduola, Taofeeq; Oyenike, Musiliu A. (Frontiers in Oncology, 2021)
Epithelial-mesenchymal transitions (EMT) are physiological programs during which polarized, immobile epithelial cells lose connection with their neighbours and are converted to migratory mesenchymal phenotype via a series of genetic and cellular events leading to the repression of epithelial-associated markers and upregulation of mesenchymal-associated markers. EMT is crucial for embryogenesis and ontogenesis during development, and wound healing. However, this process is often hijacked in pathological conditions such as tumour metastasis, which constitutes the most significant drawback in the fight against cancer, accounting for about 90% of cancer-associated mortality globally. Worse still, metastatic tumours are not only challenging to treat with the available conventional radiotherapy and surgical interventions but also resistant to several cytotoxic agents during treatment, owing to their anatomically diffuse localization in the body system. As the quest to find an effective method of addressing metastasis in cancer intervention grows, understanding the molecular interplay involving the signalling pathways, downstream effectors, and their interactions with the EMT would be an important requisite while the challenges of metastasis continue to punctuate. Unfortunately, the molecular underpinnings that govern this process remain to be completely illuminated. However, it is becoming increasingly clear that EMT, which initiates every episode of metastasis, significantly requires some microenvironment cues such as transcription factors (TFs). Therefore, this review critically examines the roles of TFs as drivers of molecular rewiring that lead to tumour initiation, progression, EMT, metastasis and colonization. It also summarizes the interaction of various signalling molecules and effector proteins with these factors and, lastly, provides insight into promising therapeutic targets that may inhibit the metastatic process.